Talc-filled polycarbonate compositions and methods for making the same

By adding ethylene interpolymer and ethylene/methyl acrylate copolymer to talc-filled polycarbonate compositions, the problem of toughness degradation caused by the reaction between talc and polycarbonate was solved, and the compositions achieved high toughness and high dart impact performance.

CN116507677BActive Publication Date: 2026-11-06DOW GLOBAL TECHNOLOGIES LLC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180078009.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-17
Filing Date
2021-12-13
Publication Date
2026-11-06
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

While talc-filled polycarbonate compositions improve rigidity and reduce the coefficient of thermal expansion, they suffer from poor toughness and dart impact resistance. In particular, the toughness of the polycarbonate composition deteriorates due to the reaction between talc and the hydroxyl groups of polycarbonate.

Method used

By introducing a specific modifier composition comprising ethylene interpolymer and ethylene/methyl acrylate copolymer, the ethylene interpolymer reacts with the hydroxyl groups of talc to inhibit polycarbonate degradation, and the ethylene/methyl acrylate copolymer provides a synergistic effect to increase dart impact performance.

Benefits of technology

It significantly improves the dart impact properties of talc-filled polycarbonate compositions, enhancing the toughness and impact resistance of the compositions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004237066680000111
    Figure BDA0004237066680000111
  • Figure BDA0004237066680000121
    Figure BDA0004237066680000121
  • Figure BDA0004237066680000122
    Figure BDA0004237066680000122
Patent Text Reader

Abstract

This invention provides talc-filled polycarbonate compositions and methods for preparing the same. The talc-filled polycarbonate composition comprises polycarbonate, talc, and a modifier composition. The modifier composition according to the embodiments disclosed herein comprises (i) 5% to 95% by weight of an ethylene interpolymer comprising copolymer units of ethylene and comonomers selected from maleic anhydride, maleic acid monoester, maleic acid diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof, and (ii) 5% to 95% by weight of an ethylene / methyl acrylate copolymer having a melt index (1 / 2) greater than 15 g / 10 min. The talc-filled polycarbonate compositions according to the embodiments disclosed herein exhibit improved dart impact.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of this disclosure generally relate to talc-filled polycarbonate compositions and methods for preparing the same, and more specifically to talc-filled polycarbonate compositions comprising a modifier composition. Background Technology

[0002] Polycarbonate compositions are plastics that can exhibit excellent properties in terms of impact resistance, heat resistance, and dimensional stability. For example, blends of polycarbonate and inorganic fillers can be used to produce molded articles requiring high rigidity. Polycarbonate is known to have high heat resistance and toughness, and when fillers such as talc are incorporated into polycarbonate, talc can increase the rigidity of the resulting polycarbonate composition and reduce its coefficient of thermal expansion. However, talc contains hydroxyl groups that can degrade polycarbonate and thus degrade the toughness of the polycarbonate composition. Therefore, there is still a need for talc-filled polycarbonate compositions that can exhibit good toughness and dart impact resistance. Summary of the Invention

[0003] The embodiments of this disclosure satisfy the aforementioned needs by providing talc-filled polycarbonate compositions comprising a specific modifier composition. The modifier composition comprises an ethylene interpolymer and an ethylene / methyl acrylate copolymer. Without being bound by theory, it is believed that the ethylene interpolymer, as described herein, can react with the hydroxyl groups of talc to inhibit the degradation of the polycarbonate, and that the ethylene / methyl acrylate copolymer, as described herein, can provide a positive synergistic effect with the ethylene interpolymer to increase dart impact.

[0004] This document discloses a talc-filled polycarbonate composition. The talc-filled polycarbonate composition comprises (a) at least 65 wt% polycarbonate; (b) 10 wt% to 30 wt% talc; and (c) 0.5 wt% to 5.0 wt% a modifier composition comprising (i) 5 wt% to 95 wt% ethylene interpolymer based on the total weight of the components in the modifier composition, said ethylene interpolymer comprising copolymer units of ethylene and comonomers selected from maleic anhydride, maleic acid monoester, maleic acid diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof; and (ii) 5 wt% to 95 wt% ethylene / methyl acrylate copolymer based on the total weight of the components in the modifier composition, said ethylene / methyl acrylate copolymer having a melt index (I2) greater than 15 g / 10 min (optionally, greater than 25 g / 10 min or greater than 35 g / 10 min).

[0005] This article also discloses a method for manufacturing talc-filled polycarbonate compositions. A method of manufacturing a talc-filled polycarbonate composition comprises mixing together: (a) at least 65 wt% polycarbonate; (b) 10 wt% to 30 wt% talc; and (c) 0.5 wt% to 5.0 wt% of a modifier composition comprising (i) 5 wt% to 95 wt% ethylene interpolymer based on the total weight of the components in the modifier composition, said ethylene interpolymer comprising copolymer units of ethylene and comonomers selected from maleic anhydride, maleic acid monoester, maleic acid diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof; and (ii) 5 wt% to 95 wt% ethylene / methyl acrylate copolymer based on the total weight of the components in the modifier composition, said ethylene / methyl acrylate copolymer having a melt index (I2) greater than 15 g / 10 min (optionally, greater than 25 g / 10 min or greater than 35 g / 10 min).

[0006] These and other implementation schemes are described in more detail in the specific embodiments. Detailed Implementation

[0007] The aspects of the disclosed polycarbonate compositions are described in more detail below. Polycarbonate compositions can be used to produce a wide variety of articles, including, for example, exterior or interior materials for household appliances, electronic products, and automobiles. However, it should be noted that this is merely an illustrative implementation of the embodiments disclosed herein. These embodiments are applicable to other technologies susceptible to similar problems described above.

[0008] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers of the same or different types. Therefore, the general term polymer encompasses the term homopolymer (used to refer to polymers prepared from only one type of monomer) and the terms copolymer or interpolymer. Trace impurities (e.g., catalyst residues) may be incorporated into and / or within a polymer. A polymer can be a single polymer, a polymer blend, or a mixture of polymers comprising a mixture of polymers formed in situ during polymerization.

[0009] The term "interpolymer" refers to a polymer prepared by polymerizing at least two different types of monomers. The term "interpolymer" includes the term "copolymer" (generally used to refer to a polymer prepared from two different monomers) and the term "terpolymer" (generally used to refer to a polymer prepared from three different types of monomers). It also covers polymers prepared by polymerizing four or more types of monomers.

[0010] The term "ethylene / methyl acrylate copolymer" refers to a polymer that contains copolymer units of ethylene monomer and methyl acrylate comonomer.

[0011] The term "(meth)acrylic acid" refers to methacrylic acid or acrylic acid.

[0012] The terms “comprising,” “including,” “having,” and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not such components, steps, or procedures are specifically disclosed. For the avoidance of any doubt, unless stated otherwise, all compositions claimed using the term “comprising” may include any additional additives, adjuvants, or compounds, whether polymerized or otherwise. In contrast, the term “substantially constitutes” excludes any other components, steps, or procedures from any subsequently listed scope, except those that are not essential for operability. The term “consisting of” excludes any ingredients, steps, or procedures not specifically described or listed.

[0013] This article discloses talc-filled polycarbonate compositions. The compositions comprise polycarbonate, talc, and a modifier composition.

[0014] There are no particular limitations on the polycarbonate in the talc-filled polycarbonate composition. In embodiments, the polycarbonate composition is a thermoplastic polycarbonate resin. The polycarbonate can be an aromatic polycarbonate prepared by reacting a carbonate precursor such as phosgene, haloformate, and diester with a diphenol. Examples of diphenols include, but are not limited to, 4,4'-bisphenol, 2,2-bis(4-hydroxyphenyl)propane, 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(3-chloro-4-hydroxyphenyl)propane, and 2,2-bis(3,5-dichloro-4-hydroxyphenyl)propane. For example, the diphenol can be 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(3,5-dichloro-4-hydroxyphenyl)propane, or 1,1-bis(4-hydroxyphenyl)cyclohexane, especially 2,2-bis-(4-hydroxyphenyl)propane, which is also known as bisphenol A. In some embodiments, the polycarbonate can be a branched polycarbonate and can be a homopolymer, a copolymer, or a blend thereof.

[0015] In an embodiment, the talc-filled polycarbonate composition comprises at least 65% by weight of polycarbonate. That is, the polycarbonate is present in an amount of at least 65% by weight based on the total weight of the talc-filled polycarbonate composition. All individual values ​​and sub-ranges of at least 65% by weight are disclosed and included herein. For example, the talc-filled polycarbonate composition may comprise at least 65% by weight, at least 70% by weight, at least 75% by weight, at least 80% by weight, or at least 85% by weight of polycarbonate, or 65% to 85% by weight, 70% to 85% by weight, 75% to 85% by weight, 80% to 85% by weight, 75% to 80% by weight, or 80% to 85% by weight of polycarbonate, wherein the weight percentage (wt%) is based on the total weight of the talc-filled polycarbonate composition.

[0016] Examples of polycarbonates suitable for embodiments of the present invention include Makrolon 2607, a polycarbonate commercially available from Covestro AG (Leverkusen, Germany).

[0017] The talc-filled polycarbonate compositions disclosed herein contain talc. There are no particular limitations on the talc in the talc-filled polycarbonate compositions. In embodiments, the talc may be synthetically manufactured talc and / or surface-treated talc.

[0018] In an embodiment, the talc-filled polycarbonate composition comprises 10% to 30% by weight of talc. That is, the talc is present in an amount of 10% to 30% by weight based on the total weight of the talc-filled polycarbonate composition. All individual values ​​of 10% to 30% by weight are disclosed and included herein. For example, the talc-filled polycarbonate composition may comprise 10% to 30% by weight, 15% to 30% by weight, 20% to 30% by weight, 25% to 30% by weight, 10% to 25% by weight, 10% to 20% by weight, 10% to 15% by weight, 15% to 25% by weight, 15% to 25% by weight, 15% to 20% by weight, or 20% to 25% by weight of talc, wherein the weight percentage (wt%) is based on the total weight of the talc-filled polycarbonate composition.

[0019] Examples of talc suitable for embodiments of the present invention include CIMPACT 710C, a talc commercially available from Imerys (Paris, France).

[0020] The talc-filled polycarbonate compositions disclosed herein include a modifier composition. This modifier composition comprises (i) 5% to 95% by weight of an ethylene interpolymer based on the total weight of the components in the modifier composition, said ethylene interpolymer comprising copolymer units of ethylene and comonomers selected from maleic anhydride, maleic monoester, maleic diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof, and (ii) 5% to 95% by weight of an ethylene / methyl acrylate copolymer based on the total weight of the components in the modifier composition, said ethylene / methyl acrylate copolymer having a melt index (I2) greater than 15 g / 10 min (optionally, greater than 25 g / 10 min or greater than 35 g / 10 min).

[0021] In embodiments, the ethylene interpolymer of the modifier composition comprises copolymer units of greater than 50% by weight of ethylene-derived units and less than 50% by weight of units derived from a comonomer selected from maleic anhydride, maleic monoester, maleic diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof (based on the total amount of polymerizable monomers). This document includes and discloses all individual values ​​and subranges of the greater than 50% by weight of ethylene-derived units and less than 50% by weight of units derived from a comonomer selected from maleic anhydride, maleic monoester, maleic diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof. For example, in some embodiments, the ethylene interpolymer comprises (a) by weight, greater than or equal to 55%, such as greater than or equal to 60%, greater than or equal to 65%, greater than or equal to 70%, greater than or equal to 75%, greater than or equal to 80%, greater than or equal to 85%, greater than or equal to 90%, greater than or equal to 92%, greater than or equal to 95%, greater than or equal to 97%, greater than or equal to 98%, greater than or equal to 99%, greater than or equal to 99.5%, from greater than 50% to 99%, from greater than 50% to 97%, from greater than 50% to 99%. 4%, from 50% to 90%, 70% to 99.5%, 70% to 99%, 70% to 97%, 70% to 94%, 80% to 99.5%, 80% to 99%, 80% to 97%, 80% to 94%, 80% to 90%, 85% to 99.5%, 85% to 99%, 85% to 97%, 88% to 99.9%, 88% to 99.7%, 88% to 99.5%, 88% to 99%, 88% to 98%, 88% to 97%, 88% to 95%, 88% to 94%, 90% (a) 99.9%, 90% to 99.5%, 90% to 99%, 90% to 97%, 90% to 95%, 93% to 99.9%, 93% to 99.5%, 93% to 99% or 93% to 97% of ethylene-derived units; and (b) less than 50% by weight, for example less than 40% or less than 30%, less than 18%, less than 15%, less than 12%, less than 10%, less than 8%, less than 5%, 0.1% to 40%, 5% to 20%, 5% to 15%, 5% to 12%, 5% to 10%, etc. 5% to 8%, 1% to 10%, 1% to 8%, 1% to 5%, 1% to 3%, 2% to 10%, 2% to 8%, 2% to 5%, 3.5% to 12%, 3.5% to 10%, 3.5% to 8%, 3.5% to 7% or 4% to 12%, 4% to 10%, 4% to 8% or 4% to 7% of units derived from a comonomer selected from maleic anhydride, maleic monoester, maleic diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof (based on the total amount of polymerizable monomers).For example, in an embodiment, the comonomer of the ethylene interpolymer is present in an amount of 5% to 15% by weight based on the total weight of the ethylene interpolymer. The comonomer content can be measured using any suitable technique, such as techniques based on nuclear magnetic resonance (“NMR”) spectroscopy, for example, by 13C NMR analysis as described in U.S. Patent No. 7,498,282 (which is incorporated herein by reference).

[0022] In the embodiments, the ethylene interpolymer is an ethylene / maleate interpolymer. Ethylene / maleate interpolymer herein refers to an interpolymer of ethylene and at least one functional comonomer selected from maleic acid monoester, maleic acid diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof. The ethylene / maleate interpolymer also includes an E / X / Y terpolymer, wherein: E is ethylene; X is a comonomer selected from maleic anhydride, maleic acid monoester, maleic acid diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof; and Y is a comonomer selected from alkyl acrylates, vinyl acetate, and (meth)acrylic acid.

[0023] The ethylene interpolymers of the modifier compositions can be obtained by high-pressure free radical polymerization. High-pressure methods suitable for carrying out the practice of this invention are described, for example, in U.S. Patent No. 4,351,931, the teachings of which are incorporated herein by reference.

[0024] In the implementation plan, the comonomer of the ethylene interpolymer is maleic acid monoester.

[0025] In embodiments, the modifier composition comprises 5% to 95% by weight of an ethylene interpolymer based on the total weight of the components in the modifier composition, the ethylene interpolymer comprising ethylene and a copolymer unit of a comonomer selected from maleic anhydride, maleic monoester, maleic diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof. All individual values ​​from 5% to 95% by weight are disclosed and included herein. For example, the modifier composition may comprise 5 to 95 wt%, 10 to 95 wt%, 15 to 95 wt%, 20 to 95 wt%, 5 to 85 wt%, 10 to 85 wt%, 15 to 85 wt%, 20 to 85 wt%, 5 to 75 wt%, 10 to 75 wt%, 15 to 75 wt%, 20 to 75 wt%, 5 to 70 wt%, 10 to 70 wt%, 15 to 70 wt%, or 20 to 70 wt% of ethylene interpolymer based on the total weight of the components in the modifier composition. The ethylene interpolymer comprises ethylene and a copolymer unit of a comonomer selected from maleic anhydride, maleic acid monoester, maleic acid diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof.

[0026] In an embodiment, the modifier composition comprises 5% to 95% by weight of an ethylene / methyl acrylate copolymer based on the total weight of the components of the modifier composition, the ethylene / methyl acrylate copolymer having a melt index (I2) greater than 15 g / 10 min (optionally, greater than 25 g / 10 min or greater than 35 g / 10 min). All individual values ​​from 5% to 95% by weight are disclosed and included herein. For example, the modifier composition may comprise 5 to 95 wt%, 10 to 95 wt%, 15 to 95 wt%, 20 to 95 wt%, 5 to 85 wt%, 10 to 85 wt%, 15 to 85 wt%, 20 to 85 wt%, 5 to 75 wt%, 10 to 75 wt%, 15 to 75 wt%, 20 to 75 wt%, 5 to 70 wt%, 10 to 70 wt%, 15 to 70 wt%, or 20 to 70 wt% of ethylene / methyl acrylate copolymer having a melt index (I2) greater than 15 g / 10 min, based on the total weight of the components of the modifier composition.

[0027] In embodiments, the ethylene / methyl acrylate copolymer of the modifier composition has a melt index (I2) greater than 15 g / 10 min. This document discloses and includes all individual values ​​and sub-ranges greater than 15 g / 10 min. For example, the ethylene / methyl acrylate copolymer of the modifier composition may have a melt index (I2) greater than 15 g / 10 min, greater than 20 g / 10 min, greater than 25 g / 10 min, greater than 30 g / 10 min, greater than 35 g / 10 min, greater than 40 g / 10 min, or greater than 45 g / 10 min, or a melt index (I2) of 15 to 500 g / 10 min, 15 to 400 g / 10 min, 15 to 300 g / 10 min, or 15 to 200 g / 10 min. Melt index (I2) within the ranges of 0 min, 15 to 100 g / 10 min, 25 to 500 g / 10 min, 25 to 400 g / 10 min, 25 to 300 g / 10 min, 25 to 200 g / 10 min, 25 to 100 g / 10 min, 35 to 500 g / 10 min, 35 to 400 g / 10 min, 35 to 300 g / 10 min, 35 to 200 g / 10 min, or 35 to 100 g / 10 min.

[0028] In an embodiment, the ethylene / methyl acrylate copolymer has a methyl acrylate content of 15% to 40% by weight based on the total weight of ethylene / methyl acrylate. All individual values ​​and sub-ranges of 15% to 40% by weight are disclosed and included herein. For example, the ethylene / methyl acrylate may have a methyl acrylate content of 15% to 40%, 15% to 30%, 15% to 25%, 20% to 40%, 20% to 30%, or 20% to 25% by weight based on the total weight of ethylene / methyl acrylate.

[0029] Examples of ethylene / methyl acrylate copolymers suitable for embodiments of the present invention include ELVALOY. TM AC15024S is commercially available from Dow Chemical Company (Midland, MI).

[0030] In embodiments, the talc-filled polycarbonate composition may contain one or more additives as known in the art. Such additives include antioxidants such as IRGANOX 1010 and IRGANOS 168 (available from BASF), UV absorbers, antistatic agents, pigments, dyes, nucleating agents, fillers, slip agents, flame retardants, plasticizers, processing aids, lubricants, stabilizers, smoke suppressants, viscosity control agents, surface modifiers, and antiblocking agents. In embodiments, the content of one or more additives ranges from 0% to 10% by weight of the talc-filled polycarbonate composition, 0% to 5% by weight of the talc-filled polycarbonate composition, 0% to 3% by weight of the talc-filled polycarbonate composition, 0.001% to 10% by weight of the talc-filled polycarbonate composition, 0.001% to 5% by weight of the talc-filled polycarbonate composition, 0.001% to 3% by weight of the talc-filled polycarbonate composition, 0.05% to 10% by weight of the talc-filled polycarbonate composition, 0.05% to 5% by weight of the talc-filled polycarbonate composition, or 0.05% to 3% by weight of the talc-filled polycarbonate composition.

[0031] The talc-filled polycarbonate compositions of the present invention can be used to form articles such as household appliances and electronic products. Such articles can be formed from any of the talc-filled polycarbonate compositions described herein.

[0032] The talc-filled polycarbonate compositions of the present invention can possess several desired properties. For example, the talc-filled polycarbonate compositions can have a dart impact greater than 11.0 Joules (J), wherein the dart impact is measured according to the test methods described below. This document includes and discloses all individual values ​​and sub-ranges greater than 11.0 J. For example, the talc-filled polycarbonate compositions can have a dart impact greater than 11.0 J, greater than 12.0 J, greater than 13.0 J, greater than 14.0 J, greater than 15.0 J, greater than 16.0 J, greater than 17.0 J, greater than 18.0 J, or greater than 19.0 J, wherein the dart impact is measured according to the test methods described below.

[0033] The dart impact of the talc-filled polycarbonate composition can also be described relative to the concentration of the component in the modifier composition. For example, without being bound by any theory, the dart impact of the talc-filled polycarbonate can increase when the amount of ethylene interpolymer in the modifier composition increases and the amount of ethylene / methyl acrylate decreases accordingly. In an embodiment where the concentration of the ethylene interpolymer as described above is greater than 15% by weight based on the total weight of the components in the modifier composition, the talc-filled polycarbonate composition can have a dart impact greater than 11.0 J, wherein the dart impact is measured according to the test method described above. In another embodiment where the concentration of the ethylene interpolymer as described above is greater than 25% by weight based on the total weight of the components in the modifier composition, the talc-filled polycarbonate composition can have a dart impact greater than 13.0 J, wherein the dart impact is measured according to the test method described above. In embodiments where the concentration of the ethylene interpolymer described above is greater than 45% by weight based on the total weight of the components in the modifier composition, or even in other embodiments, the talc-filled polycarbonate composition may have a dart impact greater than 15.0 J, wherein the dart impact is measured according to the test method described above. Furthermore, in embodiments where the concentration of the ethylene interpolymer described above is greater than 55% by weight based on the total weight of the components in the modifier composition, or even in other embodiments, the talc-filled polycarbonate composition may have a dart impact greater than 17.0 J, wherein the dart impact is measured according to the test method described above.

[0034] A method for manufacturing the talc-filled polycarbonate composition described herein is also disclosed. A method of manufacturing a talc-filled polycarbonate composition comprises mixing together: (a) at least 65 wt% polycarbonate; (b) 10 wt% to 30 wt% talc; and (c) 0.5 wt% to 5.0 wt% of a modifier composition comprising (i) 5 wt% to 95 wt% ethylene interpolymer based on the total weight of the components in the modifier composition, said ethylene interpolymer comprising copolymer units of ethylene and comonomers selected from maleic anhydride, maleic acid monoester, maleic acid diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof; and (ii) 5 wt% to 95 wt% ethylene / methyl acrylate copolymer based on the total weight of the components in the modifier composition, said ethylene / methyl acrylate copolymer having a melt index (I2) greater than 15 g / 10 min (optionally, greater than 25 g / 10 min or greater than 35 g / 10 min).

[0035] In one embodiment, a method for manufacturing a talc-filled polycarbonate composition includes melt-blending the aforementioned components (a), (b), and (c) together. In another embodiment, a method for manufacturing a talc-filled polycarbonate composition further includes extruding the components of the composition.

[0036] In an embodiment, a method of manufacturing a talc-filled polycarbonate composition comprises (1) providing a modifier composition comprising (a) 5% to 95% by weight of an ethylene interpolymer comprising copolymer units of ethylene and comonomers selected from maleic anhydride, maleic monoester, maleic diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof, and (b) 5% to 95% by weight of an ethylene / methyl acrylate copolymer having a melt index (I2) greater than 15 g / 10 min (optionally, greater than 25 g / 10 min or greater than 35 g / 10 min); and (2) blending 0.5% to 5.0% by weight of the modifier composition with 10% to 30% by weight of talc and at least 65% by weight of polycarbonate to form a talc-filled polycarbonate composition.

[0037] Test methods

[0038] Melt index (I2)

[0039] Melt index (I2) was measured at 190°C and 2.16 kg according to ASTM D-1238. Values ​​are reported in g / 10 min, corresponding to the number of grams eluted per 10 min.

[0040] Dart Impact

[0041] Samples were prepared according to the description in the following Examples section. The examples and comparative examples of the present invention were dried at 110°C for 4 hours, and then injection molded on a Krauss Maffei injection molding machine to prepare discs with a diameter of 4 inches and a thickness of 3.1 mm for instrumented dart impact testing. During the injection molding process, the temperature in different zones and the nozzle was 270-300°C, the injection pressure was 2000 bar, and the holding pressure was 200 bar. The cooling time was 40 seconds.

[0042] Each disc formed by the embodiments and comparative examples of the present invention was subjected to an instrumented dart impact test. The test method was performed according to ASTM D3763, which provides the load-to-deformation response of a plastic sheet under impact velocity under multiaxial deformation conditions. Prior to testing (according to ASTM D618), the samples were conditioned at 23°C + / - 2°C and 50% + / - 10% relative humidity (RH) for at least 40 hours and tested under the same conditions. The samples were pneumatically clamped such that the unsupported test area had a diameter of 76 + / - 3 mm. The sample dimensions were such that at least 13 mm of material was clamped. The samples were impacted with a stainless steel plunger with a diameter of 12.7 + / - 0.13 mm and a hemispherical end of the same diameter. The plunger was a free-fall gravity-driven device, wherein the impact velocity was determined by the fall height (considering friction). The impact velocity applied to the specimen was 6.66 m / s. The plunger assembly had sufficient mass such that the velocity reduction at the end of the test was less than 20%. The total impact energy is reported based on the load-displacement curve (below the area under the curve). Measurements of the dart impact are reported in Joules (J).

[0043] Example

[0044] The following examples illustrate the features of this disclosure, but are not intended to limit the scope of this disclosure.

[0045] Material

[0046] The following materials are included in the embodiments.

[0047] Makrolon 2607 is a polycarbonate commercially available from Covestro AG (Leverkusen, Germany).

[0048] CIMPACT 710C is a talc available commercially from Imerys (Paris, France).

[0049] Irganox 1010 and Irgafos 168 (“antioxidants”) are antioxidants available commercially from BASF.

[0050] ELVALOY TM AC 15024S is an ethylene / methyl acrylate copolymer with a methyl acrylate content of 24% by weight and a melt index (I2) of 50 g / 10 min.

[0051] ELVALOY TM AC 1224 is an ethylene / methyl acrylate copolymer with a methyl acrylate content of 24% by weight and a melt index (I2) of 2.0 g / 10 min.

[0052] ELVALOY TM AC 34035 is an ethylene / butyl acrylate copolymer with a butyl acrylate content of 35% by weight and a melt index (I2) of 40 g / 10 min.

[0053] ELVALOY TM AC 3427 is an ethylene / butyl acrylate copolymer with a butyl acrylate content of 27% by weight and a melt index (I2) of 4.0 g / 10 min.

[0054] The product name is ELVALOY TM Acquired commercially from AC Dow Chemical Company (Midland, MI).

[0055] Polymer 1 is a maleic anhydride-grafted ethylene acrylate copolymer with a maleic anhydride content of 1.8% by weight and a melt index (I2) of 1.8 g / 10 min.

[0056] Polymer 2 is an ethylene interpolymer with a maleic acid monoester content of 10% by weight and a melt index (I2) of 25 g / 10 min, comprising copolymer units of ethylene and maleic acid monoester comonomers. Polymer 2 can be formed by the methods and polymerization conditions provided below.

[0057] Preparation of Polymer 2

[0058] Polymer 2 is prepared in a continuous stirred tank reactor using known copolymerization techniques, wherein ethylene and a comonomer (i.e., maleic acid monoester) are introduced into the copolymerization reactor along with at least one free radical copolymerization initiator. Typical copolymerization initiators used include peroxide compounds, such as tert-butyl peracetate, tert-butyl perpentyl peroxide, tert-butyl peroctanoate, di-tert-butyl peroxide, or di-sec-butyl percarbonate. Other free radical initiators, such as azo compounds, may also be used. Typically, the initiator is present in an amount of approximately 0.0001 mol to 0.1 mol per 1,000 lbs of polymer product.

[0059] The copolymerization temperature is typically maintained between about 120 and 300°C, and preferably between about 180 and 260°C. The pressure is typically maintained between about 1300 and 3100 bar, and preferably in the range of 1650 to 2100 bar.

[0060] The copolymerization is carried out as a continuous process in which ethylene, reactive monomers, and (optionally) solvents or chain transfer agents are continuously fed into a stirred reactor along with an initiator. An example of such a stirred reaction is given in U.S. Patent 2,897,183 to Christl et al., which is incorporated herein by reference. The addition rate depends on variables such as polymerization temperature, pressure, monomers used, and the concentration of monomers in the reaction mixture. The reaction mixture is continuously removed from the autoclave, and after the reaction mixture leaves the reaction vessel, the resulting copolymer is separated from the volatile unreacted monomers by conventional means—for example, by evaporating the unpolymerized material and solvent under reduced pressure (relative to the reactor) and elevated temperature. After separation, the copolymer is typically recovered from the process as pellets, which are then blended, purged, and packaged.

[0061] Formation of the modifier composition

[0062] The modifier composition was formed by dry-blending polymers at the concentrations listed in Table 1. The polymer was fed into a Coperion ZSK-25 twin-screw extruder. The extruder was equipped with a Gala underwater granulator for granulation. The screw diameter was 24.5 mm, and the screw length to screw diameter ratio (L / D) was 48. The melt temperature was between 175°C and 185°C; the feed rate was 20 lb / h; and the screw speed was 300 RPM.

[0063] Table 1 :

[0064]

[0065]

[0066] The modifier composition, along with talc and polycarbonate, was fed into a Coperion ZSK-26 twin-screw extruder for melt blending. Talc was fed into the extruder inlet using a K-TRON T-20 feeder. The talc-filled polycarbonate composition was formed by melt blending the components via the Coperion ZSK-26 twin-screw extruder. The material was extruded through a two-hole die and passed through a 6-foot cooling water bath, then granulated using a wire cutter. The melt temperature was between 305°C and 315°C; the feed rate was 30 lb / h; and the screw speed was 300 RPM.

[0067] Table 2 below shows the weight percentages (wt%) of the embodiments (Inv.) and comparative examples (Comp.) of the present invention. As provided in Table 2, each embodiment in the examples comprises 2 wt% of a specific modifier composition, 79 wt% of polycarbonate (Makrolon 2607), 18.8 wt% of talc (CIMPACT 710C), and 0.2 wt% of antioxidants (Irganox 1010 and Irgafos 168).

[0068] Table 2 :

[0069]

[0070]

[0071] According to the test methods described above, the dart impact of certain embodiments and comparative examples of the present invention was measured. The results are reported in Table 3 below. It can be seen that when compared with polymers 2 and 1, ELVALOY, having corresponding weight percentages... TM AC1224, ELVALOY TM AC 34035 or ELVALOY TM Compared to the comparative example of AC 3427, the embodiments of the present invention (i.e., talc-filled polycarbonate compositions having a modifier composition comprising polymer 2 and ELVALOY) TM AC15024S (an ethylene / methyl acrylate copolymer with a methyl acrylate content of 24 wt% and a melt index (I2) of 50 g / 10 min) exhibits a surprisingly and significantly higher dart impact. Unbound from theoretical constraints, polymer 2 can react with the hydroxyl groups of talc to inhibit polycarbonate degradation, and ELVALOY TM AC 15024S can provide a positive synergistic effect with polymer 2 to significantly increase dart impact.

[0072] Table 3 :

[0073]

[0074] Unless expressly excluded or otherwise limited, every document cited herein (if any), including any cross-referenced or related patent or application and any patent application or patent claiming priority or benefit to this application, is hereby incorporated in its entirety by reference. No reference to any document acknowledges it as prior art to any invention disclosed or claimed herein, or as teaching, indicating, or disclosing any such invention, alone or in combination with any other referenced document. Furthermore, in the event of any conflict between the meaning or definition of any term in this document and the meaning or definition of the same term in any document incorporated by reference, the meaning or definition given to the term in this document shall prevail.

[0075] While specific embodiments of the invention have been described and illustrated, it will be apparent to those skilled in the art that many other changes and modifications can be made without departing from the spirit and scope of the invention. Therefore, it is intended that all such changes and modifications falling within the scope of the invention be covered in the appended claims.

Claims

1. A talc-filled polycarbonate composition, said composition comprising: (a) At least 65% by weight of polycarbonate; (b) 10% to 30% by weight of talc; and (c) 0.5% to 5.0% by weight of a modifier composition comprising (i) 5% to 95% by weight of an ethylene interpolymer based on the total weight of the components in the modifier composition, the ethylene interpolymer comprising ethylene and a comonomer selected from maleic anhydride, maleic monoester, maleic diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof, and (ii) 5% to 95% by weight of an ethylene / methyl acrylate copolymer based on the total weight of the components in the modifier composition, the ethylene / methyl acrylate copolymer having a melt index (I2) greater than 15 g / 10 min, wherein the melt index (I2) is measured according to ASTM D-1238 at 190°C and 2.16 kg.

2. The polycarbonate composition according to claim 1, wherein the ethylene / methyl acrylate copolymer has a melt index (I2) greater than 25 g / 10 min.

3. The polycarbonate composition according to claim 1, wherein the ethylene / methyl acrylate copolymer has a melt index (I2) greater than 35 g / 10 min.

4. The polycarbonate composition according to any one of claims 1 to 3, wherein the comonomer of the ethylene interpolymer is maleic acid monoester.

5. The polycarbonate composition according to any one of claims 1 to 3, wherein the comonomer of the ethylene interpolymer is present in an amount of 5% to 15% by weight based on the total weight of the ethylene interpolymer.

6. The polycarbonate composition according to any one of claims 1 to 3, wherein the ethylene / methyl acrylate copolymer has a methyl acrylate content of 15% to 40% by weight based on the total weight of the ethylene / methyl acrylate.

7. The polycarbonate composition according to any one of claims 1 to 3, wherein the polycarbonate composition has a dart impact of greater than 11.0 J, and the test method for the dart impact is performed according to ASTM D3763.

8. A method for manufacturing the talc-filled polycarbonate composition according to claim 1, the method comprising: Mix the following substances together: (a) At least 65% by weight of polycarbonate; (b) 10% to 30% by weight of talc; and (c) 0.5% to 5.0% by weight of a modifier composition comprising (i) 5% to 95% by weight of an ethylene interpolymer based on the total weight of the components in the modifier composition, the ethylene interpolymer comprising ethylene and a comonomer selected from maleic anhydride, maleic monoester, maleic diester, fumarate monoester, carboxylic acid, itaconic acid, fumarate, itaconic acid monoester, and combinations thereof, and (ii) 5% to 95% by weight of an ethylene / methyl acrylate copolymer based on the total weight of the components in the modifier composition, the ethylene / methyl acrylate copolymer having a melt index (I2) greater than 15 g / 10 min, wherein the melt index (I2) is measured according to ASTM D-1238 at 190°C and 2.16 kg.

9. The method according to claim 8, wherein the ethylene / methyl acrylate copolymer has a melt index (I2) greater than 25 g / 10 min.

10. The method of claim 8, wherein the ethylene / methyl acrylate copolymer has a melt index (I2) greater than 35 g / 10 min.

11. The method according to any one of claims 8 to 10, wherein the comonomer of the ethylene interpolymer is maleic acid monoester.

12. The method according to any one of claims 8 to 10, wherein the comonomer of the ethylene interpolymer is present in an amount of 5% to 15% by weight based on the total weight of the ethylene interpolymer.

13. The method according to any one of claims 8 to 10, wherein the ethylene / methyl acrylate copolymer has a methyl acrylate content of 15% to 40% by weight based on the total weight of the ethylene / methyl acrylate.

14. The method according to any one of claims 8 to 10, wherein blending is carried out by melt blending.

Citation Information

Patent Citations

  • Constant environment process for polymerizing ethylene

    US2897183A

  • Polyethylene copolymers

    US4351931A

  • Multi-layer, elastic articles

    US7498282B2

  • Thermoplastic resin composition and molded article produced therefrom

    WO2020138781A1